2008
DOI: 10.1177/1352458508095828
|View full text |Cite
|
Sign up to set email alerts
|

A pilot trial of low-dose naltrexone in primary progressive multiple sclerosis

Abstract: A sixth month phase II multicenter-pilot trial with a low dose of the opiate antagonist Naltrexone (LDN) has been carried out in 40 patients with primary progressive multiple sclerosis (PPMS). The primary end points were safety and tolerability. Secondary outcomes were efficacy on spasticity, pain, fatigue, depression, and quality of life. Clinical and biochemical evaluations were serially performed. Protein concentration of beta-endorphins (BE) and mRNA levels and allelic variants of the mu-opiod receptor gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
49
0
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(55 citation statements)
references
References 38 publications
(47 reference statements)
4
49
0
2
Order By: Relevance
“…A 6-month phase II multi-center pilot trial with LDN has been carried out in 40 patients with PPMS. A significant reduction of spasticity was observed at the end of the trial [150]. The therapeutic effect of LDN might be explained by the elevated endogenous opioids and opioid receptors due to the temporary blockade of the opioid receptors [151][152][153].…”
Section: Opioid Receptorsmentioning
confidence: 99%
“…A 6-month phase II multi-center pilot trial with LDN has been carried out in 40 patients with PPMS. A significant reduction of spasticity was observed at the end of the trial [150]. The therapeutic effect of LDN might be explained by the elevated endogenous opioids and opioid receptors due to the temporary blockade of the opioid receptors [151][152][153].…”
Section: Opioid Receptorsmentioning
confidence: 99%
“…These issues have driven patients towards alternative therapies such as low doses of naltrexone (LDN). Although LDN therapy is off-label, it has received widespread use for several autoimmune disorders including fibromyalgia, Crohn's, and MS. [6][7][8][9] Recently, several new clinical trials on LDN are have been initiated nationally and internationally. 10 Whether LDN treats symptomology or is diseasemodifying is unknown.…”
Section: Introductionmentioning
confidence: 99%
“…For MS, it is claimed that LDN may alleviate symptoms and also modify disease by slowing disability progression and reducing the relapse rate. While much of the original information about LDN and MS was based on anecdotal experiences, there are now three published clinical trials in this area [29][30][31]. These trials have produced variable results.…”
Section: Low-dose Naltrexonementioning
confidence: 94%
“…These trials have produced variable results. A study in primary-progressive MS found improvement in spasticity, worsening of pain, and no effect on multiple other outcomes, including depression, quality of life and fatigue [29]. Two other studies used similar crossover trial design in relapsing and progressive MS patients.…”
Section: Low-dose Naltrexonementioning
confidence: 96%